DAMPAK IMPLEMENTASI STEM TERHADAP MATEMATIKA DAN SAINS MELALUI LESSON STUDY: TINJAUAN PUSTAKA SYSTEMATIS - Farida Nursyahidah; Eko Retno Mulyaningrum (KALAMATIKA Jurnal Pendidikan Matematika, 2022)
STEM-based mathematics learning is required to assist learners in developing 21st-century skills, including creativity, critical thinking, communication, and cooperation. However, the application of STEM-based Mathematics and Science learning in Indonesia is relatively new and rarely done due to some obstacles. One alternative is the implementation of lesson study for the learning community. This study determines the positive impacts of STEM on Mathematics and Science learning through lesson study for the learning community based on the findings of a systematic review of current research. The results show that applying the STEM approach through lesson study positively impacts teachers and students. Positive impacts for teachers include improving lesson quality and teaching professional competency as well as improving critical and creative thinking skills, information, media and technology abilities, life and career capability, problem-solving, basic questioning skill, learning achievement, science literacy, concept understanding, and motivation as advantages for students. Nonetheless, further research is necessary to investigate the best method for applying STEM-based learning in Mathematics and Science through lesson study.